Bottom-up and top-down control in a multitrophic system: the role of nutrient limitation and infochemical-mediated predation in a plankton food-web model - Nicola D Walker; Hadi Susanto; Michael Steinke; Edward A. Codling (Indonesian Bio-Mathematical Society, 2019)
Chemicals released following herbivore grazing on primary producers can promote multitrophic interactions by influencing the foraging behaviour of higher order predators. In particular, chemicals released during microzooplankton grazing on phytoplankton can act as infochemical cues that elicit foraging responses and improve search efficiency in carnivorous copepods. Models investigating such infochemical-mediated multitrophic interactions in the plankton are typically based on top-down control, where phytoplankton concentrations are controlled through predation and grazing from higher trophic levels. However, in marine environments nutrient limitation is an important factor that influences a food-web from below, and earlier models of this system only indirectly account for this by assuming predator-free growth is logistic with a fixed carrying capacity. Here we consider the dynamics of infochemical-mediated interactions in a marine system where nutrient limitation is modelled directly through an extended NPZ-style model. We show the one-parameter bifurcation behavior of the top-down model to change when the total nutrient availability is changed, and hence demonstrate phytoplankton bloom formation to be a function of both top-down and bottom-up processes.